Peran Orang Tua Dalam Perkembangan Anak Berkebutuhan Khusus Tuna daksa: Kajian Pastoral Konseling - Wanget, Samuel; Deeker Sumolang; Mila Enjeli Salindeho; Meilani Inda Sri Dalending; Harlinda Losoh Putri Agama; David Natanael Ponto (PT. Giat Konseling Nusantara, 2024)
Children with special needs are children who are different from children in general. Children with special needs (formerly called extraordinary children) are defined as children who require special education and services to develop their human potential perfectly. Physical disability is one of the limitations for people with special needs and etymologically, physical disability is someone who has difficulty optimizing the function of their body parts as a result of injury, disease, mistreated growth, and as a result the ability to perform certain body movements is impaired. decline. Physical impairment can be defined as a form of abnormality or disability in the muscular and skeletal systems. joints and nerves caused by diseases, viruses and accidents that occur before birth, at birth and after birth. The role of parents in the development of children with special needs, such as disabled children, is very important in pastoral counseling studies. Parents have a role as educators, protectors and caregivers who influence the overall development of children. They must understand and understand the needs of children with special needs and provide appropriate guidance so that children can grow and develop optimally. In pastoral counseling studies, the role of parents also includes building self-confidence in disabled children. Parents must provide strong support and motivation so that children can improve their quality of life and improve their social and academic skills. Apart from that, parents must also understand and understand the self-concept, self-esteem, experience and education that disabled children need to increase their self-confidence.